17. Comparative Safety of Antibiotic Therapy for Outpatient Treatment of Uncomplicated Urinary Tract Infections. (31st December 2020) - Butler, Anne M; Durkin, Michael; Keller, Matthew R; Ma, Yinjiao; Powderly, William; Olsen, Margaret A
Abstract: Background: Urinary tract infection (UTI) is one of the most common indications for outpatient antibiotic prescriptions in otherwise healthy women, yet the comparative safety of antibiotics for empirical therapy is not well established. We compared the risk of adverse drug events by antibiotic treatment regimen among premenopausal women with uncomplicated UTI. Methods: Using the IBM MarketScan Commercial Database (2006–2015), we identified healthy, non-pregnant women aged 18–44 who were diagnosed with UTI and prescribed a same-day antibiotic with activity against common uropathogens. Patients were followed for outcomes with varying follow-up periods: 3 days (anaphylaxis), 14 days (acute renal failure, skin rash, urticaria/hives, nausea/vomiting, abdominal pain), 30 days (vaginitis/vulvovaginal candidiasis, non-C. difficile diarrhea) and 90 days (C. difficile diarrhea, pneumonia, tendinopathy, retinal detachment). We estimated propensity score-weighted hazard ratios (HR) and 95% confidence intervals (CI) using Cox proportional hazards models. Results: Of 1, 140, 602 eligible women, the distribution of antibiotic receipt was fluoroquinolones (44%), trimethoprim-sulfamethoxazole (TMP/SMX) (28%), nitrofurantoin (24%), narrow-spectrum β-Lactam / β-Lactamase inhibitor combinations ("β-Lactams") (3%), broad-spectrum β-Lactams (1%) and amoxicillin/ampicillin (1%). Of two first-line agents, we observed higher risk of outcomes among TMP/SMX vs. nitrofurantoin initiators: acute renal failure (HR 2.46, 95% CI 1.46–4.14), skin rash (HR 2.43, 95% CI 2.13–2.77), urticaria (HR 1.35, 95% CI 1.18–1.56), nausea/vomiting (HR 1.19, 95% CI 1.10–1.29) and abdominal pain (HR 1.14, 95% CI 1.09–1.19). Compared to nitrofurantoin, non-first-line agents (fluoroquinolones, broad-, and/or narrow-spectrum β-Lactams) were associated with higher risk of acute renal failure, skin rash, nausea/vomiting, abdominal pain, vaginitis/vulvovaginal candidiasis, diarrhea (C. difficile & non-C. difficile), pneumonia and tendinopathy. Conclusion: The risk of adverse drug events differs widely by antibiotic agent, with substantial differences in first-line agents. Understanding antibiotic safety is critical to prevent suboptimal antibiotic prescribing and reduce adverse events. Disclosures: Margaret A. Olsen, PhD, MPH, Merck (Grant/Research Support)Pfizer (Consultant, Grant/Research Support)